2009
DOI: 10.1177/112067210901900311
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent Primary Open-Angle Glaucoma and Cataract: Interim Analysis of a Trabecular Micro-Bypass Stent and Concurrent Cataract Surgery

Abstract: In patients undergoing concurrent cataract and glaucoma surgery, the iStent was safe and efficacious for the reduction of IOP and medication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 13 publications
5
80
0
7
Order By: Relevance
“…However, no attempt to reduce the number of medications preoperatively was made, potentially overestimating this effect. Compared with studies of implantation of a single stent, [8][9][10][11] use of multiple stents in this study resulted in a greater propensity to achieve a postoperative IOP of 15 mm Hg or less and a greater absolute reduction in medications. This finding is consistent with the ex vivo work of Zhou and Smedley 13 and Bahler et al 14 The use of multiple stents may exploit a greater range of circumferential flow and allow access to a greater array of collector channels to establish physiologic flow of aqueous humor into the episcleral venous system.…”
Section: Complicationsmentioning
confidence: 70%
See 2 more Smart Citations
“…However, no attempt to reduce the number of medications preoperatively was made, potentially overestimating this effect. Compared with studies of implantation of a single stent, [8][9][10][11] use of multiple stents in this study resulted in a greater propensity to achieve a postoperative IOP of 15 mm Hg or less and a greater absolute reduction in medications. This finding is consistent with the ex vivo work of Zhou and Smedley 13 and Bahler et al 14 The use of multiple stents may exploit a greater range of circumferential flow and allow access to a greater array of collector channels to establish physiologic flow of aqueous humor into the episcleral venous system.…”
Section: Complicationsmentioning
confidence: 70%
“…These postoperative findings are similar to those reported by others. [8][9][10][11]17 Further studies are needed to refine the relationship observed between the number of stents implanted with concurrent cataract surgery and IOP control. Determining the criteria for the number of stents to implant will also require further investigation.…”
Section: Complicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Genehmigung von Lippincott Williams and Wilkins) CME Der Ausgangsaugeninnendruck lag bei 21,5±3,7 mmHg unter 1,5±0,7 Medikamenten. Nach 6 Monaten betrug der Augeninnendruck (IOD) im Mittel 15,8±3,0 mmHg unter 0,5±0,8 Medikamenten, nach 12 Monaten (58 Augen, Ausgangs-IOD 21,7±3 mmHg) 17,4±3 mmHg unter 0,4±0,6 Medikamenten [11,12]. Es wurde somit eine Drucksenkung bei kombinierter Operation von 26,5 bzw.…”
Section: Zwischen Anzahl Der Eingesetzten Bypässe Und Der Fazilitätsvunclassified
“…The ocular hypotensive efficacy seen with the stent in this study was found to be consistent with the trabecular bypass mechanism of action and results described in literature. (Fea, 2010;Spiegel et al, 2008Spiegel et al, & 2009 Compared with cataract surgery alone, implantation of the iStent concomitant with cataract extraction significantly increases trabecular outflow facility, reduces IOP and the number of medications. (Fernandez-Barrientos et al, 2010) A study in cultured human anterior segments has shown that a single stent created the largest change in IOP, resulting in a mean of 12.4 ± 4.2 mm Hg, corresponding to an 84% increase in facility of outflow.…”
Section: Scientific Evidence So Farmentioning
confidence: 99%